2018
DOI: 10.1111/hex.12841
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in patient and public involvement in cancer research: A systematic review

Abstract: BackgroundPatient and public involvement (PPI) in health research is on the rise worldwide. Within cancer research, PPI ensures that the rapid development of medical and technological opportunities for diagnostics, treatment and care corresponds with the needs and priorities of people affected by cancer. An overview of the experiences, outcomes and quality of recent PPI in cancer research would provide valuable information for future research.ObjectiveTo describe the current state of PPI in cancer research foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
169
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(177 citation statements)
references
References 59 publications
8
169
0
Order By: Relevance
“…The barriers and facilitators to partnering with frail and/ or seriously ill patients (e.g., funding, infrastructure, role clarity, capacity building for both patients and researchers, structural inclusivity, trust and willingness to collaborate) are similar to those reported in other systematic and scoping reviews of patient engagement [2,12,22,28,[75][76][77]. When engaging frail and/or seriously ill patients as partners across the research cycle, the degree of illness and/or frailty, and potential instability in patients' health warrants more concern for [7, 45, 47, 51, 53-55, 62, 63, 69, 70] 11 (37%) Emotional/peer support [7, 51, 53, 55, 57, 62-64, 66, 69, 70] 5 (17%) Emotional vulnerability or emotional distress [7,47,55,71,72] 10 (33%) Incorporation of patients' priorities for research and outcomes [7,24,50,51,54,56,57,61,65,67] 8 (27%) Develop new knowledge and skills [45,51,55,59,60,62,63,71] 5 (17%) Physical/cognitive fatigue [7,47,53,55,72] 3 (10%) Acquire insights into disease and treatment [51,55,69] Researcher -Perceived Impacts…”
Section: Discussionsupporting
confidence: 55%
“…The barriers and facilitators to partnering with frail and/ or seriously ill patients (e.g., funding, infrastructure, role clarity, capacity building for both patients and researchers, structural inclusivity, trust and willingness to collaborate) are similar to those reported in other systematic and scoping reviews of patient engagement [2,12,22,28,[75][76][77]. When engaging frail and/or seriously ill patients as partners across the research cycle, the degree of illness and/or frailty, and potential instability in patients' health warrants more concern for [7, 45, 47, 51, 53-55, 62, 63, 69, 70] 11 (37%) Emotional/peer support [7, 51, 53, 55, 57, 62-64, 66, 69, 70] 5 (17%) Emotional vulnerability or emotional distress [7,47,55,71,72] 10 (33%) Incorporation of patients' priorities for research and outcomes [7,24,50,51,54,56,57,61,65,67] 8 (27%) Develop new knowledge and skills [45,51,55,59,60,62,63,71] 5 (17%) Physical/cognitive fatigue [7,47,53,55,72] 3 (10%) Acquire insights into disease and treatment [51,55,69] Researcher -Perceived Impacts…”
Section: Discussionsupporting
confidence: 55%
“…5,6 Public involvement within palliative care research can help to develop patient-focused research questions, 7,8 aid recruitment to studies, 8 and support dissemination of findings to a wider community. [7][8][9] Yet, there is a lack of evidence on the best approaches to public involvement in palliative care. Accessing the views of those who may have advanced illness and considerable disability can be challenging, and involvement can be time consuming and resource-intensive for both researchers and public contributors.…”
Section: Introductionmentioning
confidence: 99%
“…This may re ect the well-established evidence base of gendered differences in preferred learning styles and strategies [43,44]. However, it may also re ect the equally well-established evidence base that there is a gender and socio-cultural bias within the delivery of public input, where it has been shown that women, particularly in higher socioeconomic groups, were more willing to volunteer as public contributors [45]. The issue of representation in public input is frequently made more challenging when considered alongside issues such as remuneration, language, or access, all of which can act as barriers to those from poorer backgrounds or different socio-cultural backgrounds to become public contributors [46,47].…”
Section: Discussionmentioning
confidence: 98%